Organocatalytic route to the synthesis of (6S)-5,6-dihydro-6-[(2R)-2-hydroxy-6-phenylhexyl]-2H-pyran-2-one and ravensara lactones - Dwivedi, Namrata; Tripathi, Divya; Kumar, Pradeep (Tetrahedron-Asymmetry, 2011)
An organocatalytic enantioselective synthesis of the title compounds has been achieved. The stereogenic centers were generated by the iterative use of proline catalyzed alpha-aminoxylations and HWE olefination of aldehydes while the lactone ring was constructed by ring closing metathesis. (C) 2011 Elsevier Ltd. All rights reserved.

Proline catalyzed alpha-aminoxylation reaction in the synthesis of biologically active compounds - Kumar, Pradeep; Dwivedi, Namrata (Accounts of Chemical Research, 2013)
The search for new and efficient ways to synthesize optically pure compounds is an active area of research in organic synthesis. Asymmetric catalysis provides a practical, cost-effective, and efficient method to create a variety of complex natural products containing multiple stereocenters. In recent years, chemists have become more interested in using small organic molecules to catalyze organic reactions. As a result, organocatalysis has emerged both as a promising strategy and as an alternative to catalysis with expensive proteins or toxic metals. One of the most successful and widely studied secondary amine-based organocatalysts is proline. This small molecule can catalyze numerous reactions such as the aldol, Mannich, Michael addition, Robinson annulation, Diels-Alder, alpha-functionalization, alpha-amination, and alpha-aminoxylation reactions. Catalytic and enantioselective alpha-oxygenation of carbonyl compounds is an important reaction to access a variety of useful building blocks for bioactive molecules. Proline catalyzed alpha-aminoxylation using nitrosobenzene as oxygen source, followed by in situ reduction, gives enantiomerically pure 1,2-diol. This molecule can then undergo a variety of organic reactions. In addition, proline organocatalysis provides access to an assortment of biologically active natural products including mevinoline (a cholesterol lowering drug), tetrahydrolipstatin (an antiobesity drug), R(+)-alpha-lipoic acid, and bovidic acid. In this Account, we present an iterative organocatalytic approach to synthesize both syn- and anti-1,3-polyols, both enantio- and stereoselectively. This method is primarily based on proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons (HWE) olefination of aldehyde to give a gamma-hydroxy ester. In addition, we briefly illustrate the broad application of our recently developed strategy for 1,3-polyols, which serve as valuable, enantiopure building blocks for polyketides and other structurally diverse and complex natural products. Other research groups have also applied similar strategies to prepare such bioactive molecules as littoralisone, brasoside and (+)-cytotrienin A. Among the various synthetic approaches reported for 1,3-polyols, our organocatalytic iterative approach appears to be very promising and robust. This method combines the merit of organocatalytic reaction with an easy access to both enantiomerically pure forms of proline, mild reaction conditions, and tolerance to both air and moisture. In this Account, we present the latest applications of organocatalysis and how organic chemists can use this new tool for the total synthesis of complex natural products

Transition metal catalysis-a unique road map in the stereoselective synthesis of 1,3-polyols - Kumar, Pradeep; Tripathi, Divya; Sharma, Brijesh M.; Dwivedi, Namrata (Organic & Biomolecular Chemistry, 2017)
The present review summarizes recent diverse reactions employed in the formation of 1,3-polyols providing an overview of the mechanistic pathway and the enantioselectivity obtained, in terms of the properties of transition metals directly involved in the catalytic transformations and their interaction with various ligands.